Transcultural justice at the Tokyo Tribunal: the Allied struggle for justice, 1946-48 - Lingen, Kerstin von (History of warfare, 2018)
While the International Military Tribunal at Nuremberg has been at the centre of scholarly attention, the Tokyo Tribunal has for decades been neglected. This is surprising insofar as this tribunal was a well-organized Allied endeavour and prefigured the International Courts of our day. Eleven national teams were sent to Tokyo between 1946 and 1948 to bring about justice in the aftermath of the Pacific War. This volume offers an innovative approach to the Tokyo Tribunal as an arena of transcultural engagement, and contextualizes legal agents as products of transnational forces, constituted through dialogues about legal concepts and processes of faction-making. The endeavor was challenged by different national policies, divergent legal traditions, and varying cultural perceptions of the task ahead